2016
DOI: 10.3389/fmicb.2016.01285
|View full text |Cite
|
Sign up to set email alerts
|

Biotic Interactions in Microbial Communities as Modulators of Biogeochemical Processes: Methanotrophy as a Model System

Abstract: Microbial interaction is an integral component of microbial ecology studies, yet the role, extent, and relevance of microbial interaction in community functioning remains unclear, particularly in the context of global biogeochemical cycles. While many studies have shed light on the physico-chemical cues affecting specific processes, (micro)biotic controls and interactions potentially steering microbial communities leading to altered functioning are less known. Yet, recent accumulating evidence suggests that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 100 publications
2
78
0
Order By: Relevance
“…An essential question in understanding co‐occurrence patterns is identifying the ecological mechanisms that underlie species co‐existence and mutual exclusion. Microbial co‐occurrence networks, mainly reconstructed from amplicon sequencing data, are being increasingly used to infer significant associations between pairs of co‐occurring taxa and often ascribed to biological interactions (Faust & Raes, ; Fuhrman, Cram, & Needham, ; Ho et al, ; Pérez‐Valera et al, ). Critical voices, however, call for caution when analysing and interpreting co‐occurrence networks in order to avoid the description of ecologically meaningless interactions (Barner et al, ; Connor, Barberán, & Clauset, ; Freilich et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…An essential question in understanding co‐occurrence patterns is identifying the ecological mechanisms that underlie species co‐existence and mutual exclusion. Microbial co‐occurrence networks, mainly reconstructed from amplicon sequencing data, are being increasingly used to infer significant associations between pairs of co‐occurring taxa and often ascribed to biological interactions (Faust & Raes, ; Fuhrman, Cram, & Needham, ; Ho et al, ; Pérez‐Valera et al, ). Critical voices, however, call for caution when analysing and interpreting co‐occurrence networks in order to avoid the description of ecologically meaningless interactions (Barner et al, ; Connor, Barberán, & Clauset, ; Freilich et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, pathogen success was lower when resident networks had low nestedness (or modularity, see Box 1) and high connectance, presumably through more efficient consumption of resources. Other recent studies found that associations between methane oxidising bacteria and other microbes were central in modulating methane-oxidation (Ho et al 2016), and that fungal co-occurrence network structure was strongly associated with different stages of litter decomposition (Purahong et al 2016). Thus, new ecological knowledge of the structure of interactive networks among organisms and their environment might be used as an indicator of their functional attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies found that associations between methane oxidising bacteria and other microbes were central in modulating methane‐oxidation (Ho et al . ), and that fungal co‐occurrence network structure was strongly associated with different stages of litter decomposition (Purahong et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Methanotroph diversity may buffer ecosystem functioning during environmental fluctuations [58][59][60]. Methanotrophs isolated from environmental samples typically exhibit distinct temperature optima.…”
Section: Discussionmentioning
confidence: 99%
“…In natural systems, the diversity of even remote taxa often co-varies [10,61], so that BEF relationships observed in such systems reflect the compound effects of diversity changes across multiple, potentially interacting, taxonomic groups. Methanotrophs require other microorganisms for sustained growth [60,62], most likely to remove metabolites that otherwise accumulate to inhibitory levels. Recent experiments also have shown that volatiles produced by heterotrophs, specifically dimethyl sulfides, can promote methanotrophic growth even if heterotrophs are physically isolated [63].…”
Section: Discussionmentioning
confidence: 99%